Initial premium of IPOs and the immediate aftermarket behaviour of investors: evidence from Malaysian IPOs / Othman Yong - Yong, Othman (Universiti Teknologi MARA, Negeri Sembilan, 2012)
This paper examines the significance of some ex-ante variables of Malaysian IPOs on the initial premium and the immediate aftermarket behaviour of investors, during the period of January 2004 to July 2009.